Understanding the complications of pseudomonas aeruginosa biofilm exudates on wound healing - Teo, Erica Mei Ling (Nanyang Technological University, 2020)
This thesis illustrates the effects of secreted factors of Pseudomonas aeruginosa biofilm exudates on different wound healing responses of fibroblasts and keratinocytes in vitro and in an in vivo murine wound healing model. A dose-dependent effect of P. aeruginosa PAO1 biofilm conditioned media (BCM) on cell migration was observed. At moderate to high concentrations of PAO1 BCM (30-100 %), migration was hampered, together with a loss of cell viability in vitro. PAO1 BCM at low doses (1 10 %) may be able to promote migration. Differences in responses after 50 % PAO1 BCM incubation between fibroblasts and keratinocytes were also observed, with keratinocytes being more susceptible to the cytotoxic secreted factors and experiencing less loss in cell adhesion compared to fibroblasts in vitro. Occludin levels were decreased in both cell types after 50 % PAO1 BCM challenge. Cx43, β-catenin and N cadherin levels were reduced in fibroblasts. The in vivo model revealed that 100 % PAO1 BCM challenge did not result in significant changes in wound sizes and E cadherin junctions from controls. Interestingly, re-epithelialisation was hampered, with a concomitant decrease in leukocyte infiltration at the wound edge. The downregulation of inflammatory responses by PAO1 BCM was correlated to a decrease in p65/p50 heterodimer and unchanged IκB-α levels, showing that the NF-κB pathway was not activated. Further investigations revealed that p65 may have been degraded by the proteasome. The dampened NF-κB pathway was correlated with a decrease in JNK1 and c-Jun levels. The effects of PAO1 BCM on keratinocyte differentiation were also checked due to the close association of this pathway with the NF-κB pathway. Early and late keratinocyte differentiation were impaired in vitro and in vivo. Identification of the secreted factors that caused these effects was attempted via biochemical tests. Preliminary data showed that the possible factors involved in cytotoxicity were heat sensitive around 100 ℃, non-proteinaceous and neither were they LasB, RhlA, LasR nor LPS. Future work should identify these factors. This study highlights the importance of secreted biofilm factors in complicating chronic wound closure and underlines the potential of targeting these factors for more effective therapies.